Real-life drug persistence in patients with rheumatic diseases treated with CT-P13: a prospective observational cohort study (PERSIST). Issue 2 (23rd April 2021) - Taylor, Peter C; Christensen, Robin; Moosavi, Shahrzad; Selema, Pamela; Guilatco, Ruffy; Fowler, Heather; Mueller, Markus; Liau, Katherine F; Haraoui, Boulos
Abstract: Objective: The aim was to report results from PERSIST, a real-life, observational, prospective cohort study of CT-P13, an infliximab (IFX) biosimilar, for treatment of patients with RA, AS or PsA who were biologic naïve or switched from an IFX reference product (IFX-RP; Remicade). Methods: Adult patients were recruited during usual care at 38 sites in Europe and Canada and enrolled by their physicians after meeting eligibility criteria according to the country-approved label for CT-P13. Primary outcomes were to determine drug utilization and treatment persistence and to assess safety. Patients were followed for up to 2 years. Data were analysed and reported descriptively. Results: Of 351 patients enrolled, 334 were included in the analysis (RA, 40.4%; AS, 34.7%; PsA, 24.9%). The safety analysis set comprised all 328 patients treated with CT-P13. The majority (58.2%) of patients received CT-P13 monotherapy, most (72.6%) by dosing every 6 or 8 weeks. The mean treatment persistence was 449.2 days; 62.3% of patients completed 2 years of treatment. In all, 214 treatment-emergent adverse events (TEAEs) were reported in 38.4% of patients. Most TEAEs were of mild or moderate intensity; 13 were severe. The most commonly reported TEAEs were drug ineffective (9.5%) and infusion-related reactions (5.2%). The most frequently reported infection-related TEAEs were upper respiratory tract infections (3.0%), nasopharyngitis (2.1%) and bronchitis (1.5%). No patients experienced tuberculosis. Conclusion: Drug utilization and treatment persistence with CT-P13 were consistent with historical reports of IFX-RP in this patient population. Safety findings did not identify new concerns for CT-P13 in the treatment of patients with RA, AS or PsA. Trial registration: ClinicalTrials.gov: NCT02605642.